Съвременни нагласи към съотношението писмен: устен български език - Алексова, Красимира (Slavica Lodziensia, 2019)
The study analyses answer given to three questions part of a nationally representative survey on linguistic attitudes towards written grammatical norms. These questions are aimed at gathering information about the possible attitudes of modern Bulgarians towards the magnitude distance between the Bulgarian written standard language and oral speech. Another aim of the study is to explore respondents‘ preferences concerning the question of synchronization between the two existing language forms - written and oral. The survey clearly shows that more than 61% of respondents are of the opinion that the differences between the Bulgarian written and spoken language should be decreased, respectively, there needs to be a process of convergence and equalization of the two language codes. The study applies the hyper-square method in order to explore which socio-demographic factors have a major influence on respondents‘ attitudes. The domineering view (69% of the respondents) is that oral speech should be in line with the Bulgarian written standard language, consequently, grammatical rules should be followed and taken on board when speaking. Finally, the chi-square method is applied when defining the factors which determine the respondents‘ attitudes. The study introduces the idea that conservative attitudes are likely to appear amongst Bulgarian adults as they have the idea of decreasing the differences between the Bulgarian written and oral language by finding a way of synchronizing them.